An engineering approach for a T-joint fillet welding simulation using simplified material properties. (1st December 2016) - Perić, Mato; Tonković, Zdenko; Garašić, Ivica; Vuherer, Tomaž
Abstract: In the present study, a three-dimensional numerical simulation of a T-joint fillet welding of two plates is performed using simplified material properties. To investigate the influence of the temperature-dependent thermo-mechanical material properties of carbon steel on the transient temperature distributions and weld-induced residual stresses and deformations, two different cases are considered. In the first case, all the material properties, except the yield stress, are taken as constant at room temperature. In the second case, to calculate the temperature-dependent material properties, the polynomials defined by the ASCE manual are used. From the simulation results, it is concluded that, compared with the reference case that uses the true properties of the chosen material S355JR, the first case of simplification is more suitable for the prediction of plate deflections, while the second case is more favorable for the assessment of thermal fields, heat-affected zones, residual stress fields and stress intensity factors. Highlights: ASCE polynomials are suitable for thermal field calculation in carbon steel. ASCE polynomials are suitable for residual stress calculation in carbon steel. Thermal expansion coefficient has significant influence on structure deflection. ASCE polynomials are suitable for HAZ size calculation in carbon steel.